2008
DOI: 10.1016/j.actatropica.2008.03.013
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Entamoeba moshkovskii in a Tanzanian HIV population

Abstract: Entamoeba moshkovskii and Entamoeba dispar are microscopically indistinguishable from the pathogenic species Entamoeba histolytica. There are limited data on the prevalence of these commensal infections from Africa. We utilized PCR and antigen detection to evaluate the carriage rate of E. moshkovskii, E. dispar, and E. histolytica infection in stool from a cohort of HIV-suspected or confirmed inpatients from Tanzania. Entamoeba histolytica was detected by ELISA in 4% (5/118) while Entamoeba moshkovskii and E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 8 publications
3
30
2
Order By: Relevance
“…The fact is that infection with E. moshkovski is not uncommon and has a higher prevalence than infection with E. histolytica. The same was found in India (Parija and Kairnar, 2005), in homosexual patients with gastrointestinal symptoms in Australia (Fotedar et al, 2008), in two healthy adults in Tunisia (Ben Ayed et al, 2008a), and in a cohort of HIV-suspected or confirmed patients in Tanzania (Beck et al, 2008). All these studies also highlighted the important prevalence of E. moshkovski mono infection.…”
Section: Global Distributionsupporting
confidence: 51%
“…The fact is that infection with E. moshkovski is not uncommon and has a higher prevalence than infection with E. histolytica. The same was found in India (Parija and Kairnar, 2005), in homosexual patients with gastrointestinal symptoms in Australia (Fotedar et al, 2008), in two healthy adults in Tunisia (Ben Ayed et al, 2008a), and in a cohort of HIV-suspected or confirmed patients in Tanzania (Beck et al, 2008). All these studies also highlighted the important prevalence of E. moshkovski mono infection.…”
Section: Global Distributionsupporting
confidence: 51%
“…More reliable data on the prevalence and pathogenesis of E. moshkovskii infection are needed to discern the potential role of this amoeba as an entropathogen (Tanyuksel et al, 2007). Conversely, some other reports support the commensal nature (Beck et al, 2008). SolaymaniMohammadi et al (2006) found one E. moshkovskii from apparently healthy person in Iran (SolaymaniMohammadi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…9 Since then, human isolates of E moshkovskii have been reported from at least 13 other countries, including both resource-poor and resource-rich countries: the United States, Italy, South Africa, India, Australia, Pakistan, Iran, Tanzania, Turkey, Malaysia, Thailand, Tunisia, and the United Arab Emirates. 9,[21][22][23][24][25][26][27][28][29][30][31][32][33] In most of these studies the ameba has not been associated with disease and was isolated from very few individuals. However, high prevalences of E moshkovskii were reported in some countries: 50% in Australia, 23 24.9% and 15.6% in 2 different study populations in India, 34,35 21.1% in Bangladesh, 9 13.2% in Tanzania, 26 13.2% in Pakistan, 24 and 5.2% in Iran.…”
Section: Entamoeba Disparmentioning
confidence: 99%
“…9,[21][22][23][24][25][26][27][28][29][30][31][32][33] In most of these studies the ameba has not been associated with disease and was isolated from very few individuals. However, high prevalences of E moshkovskii were reported in some countries: 50% in Australia, 23 24.9% and 15.6% in 2 different study populations in India, 34,35 21.1% in Bangladesh, 9 13.2% in Tanzania, 26 13.2% in Pakistan, 24 and 5.2% in Iran. 25 Although previous reports on the identification of E moshkovskii in fecal samples had not shown any association with clinical illness, recent studies from Bangladesh, 8,9 India, 34,35 and Pakistan 24 reported E moshkovskii in patients with gastrointestinal symptoms, such as diarrhea or dysentery, and with no other known pathogens, raising questions about the long-accepted status of this organism as nonpathogenic.…”
Section: Entamoeba Disparmentioning
confidence: 99%